Perioperative Glucose Control and Infection Risk in Older Surgical Patients - Lee, Pearl (Curr Geriatr Rep, 2014)
The aging of the U.S. population is leading to an increasing number of surgical procedures performed on older adults. At the same time, the quality of medical care is being more closely scrutinized. Surgical site infection is a widely-assessed outcome. Evidence suggests that strict perioperative serum glucose control among patients with or without diabetes can lower the risk of these infections, but it is unclear whether this control should be applied to older surgical patients. In this clinical review, we discuss current research on perioperative serum glucose management for cardiothoracic, orthopedic, and general/colorectal surgery. In addition, we summarize clinical recommendations and quality-of-care process indicators provided by surgical, diabetes, and geriatric medical organizations.